Pengaruh Konflik Internal, Stres Kerja Dan Lingkungan Kerja Terhadap Produktivitas Karyawan (Studi Kasus PT. Citra Lencana Sakti) - Lely Susmika; Mayroza Wiska; Yesi Gusteti (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2022)
Abstract: The type of research used in this study is quantitative research, the sample in this study is employees at PT. Citra Lencana Sakti, totaling 75 employees, this sampling uses non-probability sampling, the sampling technique used is quota sampling. The tool used to collect data is a questionnaire. The data were analyzed using SPSS, namely using the Validity Test, Reliability Test, Mucticolinierity Test, Normality Test, Heteroscedasticity Test, R2 Determination Coefficient Test, Simultaneous Significant Test (Statistical Test F), Individual Parameter Significant Test (Test Statistics t). The results of the study partially show that the dependent variable is internal conflict (X1), work stress (X2) has a positive and significant effect on employee productivity, and the work environment (X3) has no and no significant effect on employee productivity. and the results of simultaneous research where Fcount is greater than Ftable then H0 is rejected and H1 is accepted, then internal conflict, work stress and work environment have a significant effect on employee productivity. Keywords: Conflict, Stress and Environment Work Productivity